Efeitos do extrato aquoso de abajeru (Crhysobalanus icaco) sobre o peso corporal, adiposidade e sensibilidade à insulina de camundongos obesos - White, Pollyanna Alves Secundo (2011)
Obesity is characterized by excessive accumulation of fat in the body. The anatomical location of the tissue, more specifically its abdominal (visceral) distribution, plays a major role in the development of insulin resistance, which acts as a key point linking obesity to the development of several other chronicle diseases. Thus, research on new therapies that may positively affect the development and treatment of obesity and its co morbidities are needed. This study aimed at investigating the potential of aqueous extract of Chrysobalanus icaco leaves (EACI) on the loss of weight and adipose tissue, and assessing its effects on insulin sensitivity in obese mice. Therefore, we used 34 Swiss mice divided into four groups which received a standard diet (SD), standard diet plus EACI (DPE), high-fat diet (HFD) and high-fat diet plus EACI (DHE), which was mixed to the drinking water of animals during the last 4 weeks of a total of 14weeks in which they received their diets. At the end of the experiment consumption, body weight, weight of fat pads, blood glucose, serum lipids, insulin sensitivity and glucose tolerance were evaluated. The results showed that the HC group had significant higher body mass (p < 0,001), fat pads (p < 0,0001), feed efficiency (p < 0,0001) and blood glucose levels (p< 0,05), besides higher area under curve (p < 0,05) on the insulin tolerance test. After the 4th week of treatment, in the HAD group, the EACI promoted less weight gain (p < 0,05), blood glucose (p <0.05) and insulin sensitivity (p <0.05) normalization, despite the high-fat diet intake. Regarding the adipose tissue there was little effect caused by the extract and no effect on the serum lipids and glucose tolerance. Thus, the data indicates that a model of high-fat induced obesity associated with insulin resistance was validated and that the extract was capable of normalizing the blood glucose levels and insulin sensitivity and still prevented the weight gain in the obese animals.